Partitioning of oblique convergence coupled to the fault locking behavior of fold‐and‐thrust belts: Evidence from the Qilian Shan, northeastern Tibetan Plateau. Issue 9 (2nd September 2017) - Allen, Mark B.; Walters, Richard J.; Song, Shuguang; Saville, Christopher; De Paola, Nicola; Ford, Jonathan; Hu, Zhenxing; Sun, Wenli
Abstract: Oblique plate convergence is common, but it is not clear how the obliquity is achieved by continental fold‐and‐thrust belts. We address this problem in the Qilian Shan, northeastern Tibetan Plateau, using fieldwork observations, geomorphic analysis, and elastic dislocation modeling of published geodetic data. A thrust dips SSW from the northern range front and underlies steeper thrusts in the interior. Cenozoic thrust‐related shortening across the Qilian Shan is 155–175 km, based on two transects. Elastic dislocation modeling indicates that horizontal strain in the interseismic period is consistent with oblique slip on a single low‐angle detachment thrust below 26 km depth, dipping SSW at 17°. We suggest that this detachment is located above North China Block crust, originally underthrust during Paleozoic orogeny. Horizontal shear strain is localized directly above the updip limit of creep on the detachment and is coincident with the left‐lateral Haiyuan Fault. This configuration implies that oblique slip on the detachment below seismogenic depths is partitioned in the shallow crust onto separate strike‐slip and thrust faults. This is consistent with strain partitioning in oceanic subduction zones but has not previously been found by dislocation models of continental interiors. The marginal, strike‐slip, Altyn Tagh Fault influences thrusting within the Qilian Shan for 100–200 km from the fault but does not control the regional structure, where Paleozoic basement faults have been reactivated. The Qilian Shan resembles the main Tibetan Plateau in nascent form: active thrusts are marginal to an interior that is developing plateau characteristics, involving low relief, and low seismicity. Key Points: Oblique active convergence across the Qilian Shan fold‐and‐thrust belt occurs by strain partitioning, similar to oblique subduction zones Interseismic crustal velocities are consistent with oblique motion on a single detachment thrust below 26 km depth Geomorphic and seismicity aspects of the Qilian Shan resemble a nascent orogenic plateau Plain Language Summary: Tectonic plates commonly converge obliquely, meaning that the convergence direction is not head‐on to the boundary between the two plates but slanted at an angle. This behavior is best known and understood from where an oceanic plate passes underneath another plate margin. The interiors of continents can also deform obliquely, but the deformation is not so well understood. In this study we have looked at the faults across a mountain range at the northeastern side of the Tibetan Plateau, the Qilian Shan, to understand how the oblique convergence takes place. Part of our work involves looking at the structures on the ground and through satellite imagery, and part reanalyses data previously gathered for the active rates of convergence across the range. The approaches give complementary results, in that the oblique convergence seems to be split into two components, one dipping under the range and one slicing along it. The data for the active slip place the range‐parallel slicing above the point where the underlying, dipping, fault changes behavior, from earthquake‐prone to earthquake‐free. In this respect the Qilian Shan deforms remarkably simply, even though the continents are typically more complex than oceanic plates.